2018
DOI: 10.1021/acscatal.7b03777
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Microenvironments of the Metal–Ionic Liquid Interface during Electrochemical CO2 Reduction

Abstract: Recently, many experimental and theoretical efforts are being intensified to develop high-performance catalysts for electrochemical CO 2 conversion. Beyond the catalyst material screening, it is also critical to optimize the surrounding reaction medium. From vast experiments, inclusion of room-temperature ionic liquid (RTIL) in the electrolyte is found to be beneficial for CO 2 conversion; however, there is no unified picture of the role of RTIL, prohibiting further optimization of the reaction medium. Using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 42 publications
8
97
0
Order By: Relevance
“…The majority of the studies published in this field have utilized Ag materials of varying morphology (planar surfaces, nanoparticles, nanowires, metal foams, etc.) as primary CO 2 RR catalysts in ILs, whereas other electrode materials have scarcely been studied …”
Section: Introductionsupporting
confidence: 88%
“…The majority of the studies published in this field have utilized Ag materials of varying morphology (planar surfaces, nanoparticles, nanowires, metal foams, etc.) as primary CO 2 RR catalysts in ILs, whereas other electrode materials have scarcely been studied …”
Section: Introductionsupporting
confidence: 88%
“…This meanst hat electron transfer to the electrode surface in [Bmim][124Triz] is more facile, which can enhance the current density. [23] Additionally,p revious works presumed that the monolayer formed by ILs on the electrode surfacep layed ak ey role in CO 2 reduction and inhibiting H 2 formation on the cathode surface. We found that the resistance of the absorbed film on the cathode surface (R f )w as only 0.7 W cm À2 ,w hichs uggested that the reaction species could be easily transferred through the IL monolayer.T hese results provide sufficient support to the excellent performance of CO 2 electroreduction in the superbasicI L.…”
Section: Resultsmentioning
confidence: 99%
“…Rosen et al [92] investigated the limitations of water addition to ionic liquids and show that additions of up to 30 mol/liter of water to EMIm-BF 4 do not significantly influence amount of hydrogen Catal., 2018, 8, 2420-2427. [90] Copyright 2018 American Chemical Society. [97] produced.…”
Section: Co 2 Reduction In Electrolyte Mixturesmentioning
confidence: 99%